2015
DOI: 10.1111/ecc.12382
|View full text |Cite
|
Sign up to set email alerts
|

Renegotiating hope while living with lymphoedema after cancer: a qualitative study

Abstract: Hope is defined as a multi-dimensional life force, a coping resource and a necessity for coping with illness. Concepts of normalcy, hope and loss are explored in this qualitative study and positioned within recent scholarship on hope in cancer survivors. The experiences of 13 participants (11 women, 2 men) in two Canadian provinces who were living with lymphoedema secondary to cancer were analysed. For these participants, hope assumed various meanings. For some, hope was seen as passive inaction, whereas hope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
(74 reference statements)
1
19
0
Order By: Relevance
“…Whether this association is due to colorectal cancer or the physical changes associated with colorectal cancer bears further investigation. For example, people living with lymphoedema, a disease that also has significant physical changes, also report a strong desire to return to normal (Hamilton & Thomas, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this association is due to colorectal cancer or the physical changes associated with colorectal cancer bears further investigation. For example, people living with lymphoedema, a disease that also has significant physical changes, also report a strong desire to return to normal (Hamilton & Thomas, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to sustain activities that were valued before the cancer diagnosis is also associated with hope. Qualitative studies that have demonstrated valued activities with hope include: 13 Canadians living with lymphoedema associated with cancer (Hamilton & Thomas, 2016), 17 people with advanced cancer in Hong Kong (Mok et al, 2010) and 50 people treated for cancer in a London outpatient clinic (Sanatini, Schreir, & Stitt, 2008). Each of these qualitative studies were conducted on people with different cancers and in different sites, suggesting that functional well-being may contribute to hope.…”
mentioning
confidence: 99%
“…It is essential to acknowledge however that not all participants reported having a positive perceived change to QoL since having LVA, and the disappointment was palpable. Hamilton and Thomas (2016) found that cancer survivors' renegotiated hope after being diagnosed with lymphoedema, and the object of desire was a return to normal. However, due to the hype of LVA being a 'cure' for lymphoedema, some participants had unrealistic expectations of returning to normal.…”
Section: The Impact Of Lvamentioning
confidence: 99%
“…Nevertheless, awareness of early symptoms is important, as is information on self-management strategies for oral cancer survivors, who often live with significant morbidity including facial disfigurement; Badr et al (2016) demonstrate some interesting findings through use of a web-based strategy targeting both oral cancer patients and their family caregivers. Finally, take a look at Hamilton and Thomas's (2016) paper on the experiences of patients with lymphoedema-a condition which can be associated with significant morbidity and distress in cancer patients. Management of lymphoedema has improved significantly in recent years, and this paper presents a very positive outlook on meeting the challenges of this condition.…”
Section: The Eu and Cancer Researchmentioning
confidence: 99%